2003
DOI: 10.3748/wjg.v9.i1.99
|View full text |Cite
|
Sign up to set email alerts
|

Nested case-control study on the risk factors of colorectal cancer

Abstract: The study suggested that mucous blood stool history and mixed sources of drinking water were the risk factors of colon cancer and rectal cancer. There was no any significant association between dietary habits and the incidence of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…The study population involved all residents aged 30 years or older in 10 small towns, and is described elsewhere [8]. At baseline, the cohort members were invited to screen for CRC using the Reverse Passive Hemagglutination Assay-Fecal Occult Blood Test (RPHA-FOBT) [9].…”
Section: Cohortmentioning
confidence: 99%
“…The study population involved all residents aged 30 years or older in 10 small towns, and is described elsewhere [8]. At baseline, the cohort members were invited to screen for CRC using the Reverse Passive Hemagglutination Assay-Fecal Occult Blood Test (RPHA-FOBT) [9].…”
Section: Cohortmentioning
confidence: 99%
“…A reduction of CRC mortality in the Unites States was interpreted as due to an increase in colonoscopies for earlier detection (5,6), and a reduction by 43% in people attending once-only flexible sigmoidoscopy screening in the United Kingdom (7) also reveals a bright future for success in CRC prevention and control. In China, since 1980s, a protocol of CRC screening in Chinese was established and proved by a reduction of CRC mortality with a randomized controlled trial in 2003 (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, colorectal cancer is one of the major causes of morbidity and mortality leading to approximately 10% of the total cancer cases among both males and females [1,2]. The incidence of colorectal cancer has been increasing all over the world with more than 500,000 cases being diagnosed every year [1].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing trend of colon and rectal cancers have been observed among men and women from the Indian subcontinent, the incidence being about 4 per 100,000 population for both sexes together and is the fifth most common cancer (64,332; 6.3%) in this population [3]. The studies from China and Saudi Arabia have identified various risk factors for colorectal cancer such as age >50 years, male gender, illiteracy, dietary pattern, and genetic factors such as family history of colorectal and other cancers [1,4]. However, there are scant data with regard to this from this coastal region with its unique dietary pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation